Provably secure partially blind signature without trusted PKG - FENG Tao1; PENG Wei1; MA Jian-feng3 (Tongxin xuebao)
Using gap Diffie-Hellman groups, based partially blind signature scheme, an efficient ID-based partially blind signature scheme without trusted private key generator （PKG） was proposed. In this scheme, PKG was prevented from forging a legal user’s signature because it only generated partial private key. Under the random oracle model, the proposed scheme was proved to be secure against existential forgery on adaptively chosen message and ID attack. The security of scheme relied on the hardness of the computational Diffie-Hellman problem （CDHP）. The proposed scheme satisfies security properties: correctness and partial blindness. Compared with the Chow et al.’s scheme, the new scheme needs less computational cost and is more efficient.